Flame-retardant polyurethane resin as well as preparation method and application thereof

The tridiol phosphite and hydroxyethylaziridine modified rosin resin prepared by transesterification method solve the problem of insufficient flame retardancy and toughness of large tower resin materials, and realizes a two-component polyurethane resin with high strength, aging resistance and high impact toughness, which is suitable for the preparation of composite poles.

CN119505164APending Publication Date: 2025-02-25南京聚发新材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411647001.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to develop a new resin material that can meet the requirements of large tower winding processes, with excellent flame retardant properties and toughness to solve the problem of tower breakage caused by low toughness of traditional resins.

Method used

Tridiol phosphite esters were prepared as flame retardant and solvent by transesterification method, rosin was dissolved and hydroxyethylaziridine was added. By reacting a carboxylic acid group with aziridine group, a rosin modified polymer containing binary active hydrogen and conjugated double bonds was obtained, and it was applied to two-component polyurethane resin.

Benefits of technology

It realizes the long-term operation time of the resin and is insensitive to air. The cured substances and fiber-reinforced composites have excellent impact toughness and high flame retardant properties, which fully meet the production process requirements of large poles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139929600000031
    Figure BDA0005139929600000031
  • Figure BDA0005139929600000032
    Figure BDA0005139929600000032
  • Figure BDA0005139929600000071
    Figure BDA0005139929600000071
Patent Text Reader

Abstract

The invention discloses flame-retardant bi-component aliphatic polyurethane resin as well as a preparation method and application thereof. The resin is prepared by mixing a component S1 and a component S2, wherein the molar ratio of the mole number of reactive hydroxyl groups in the component S1 to the mole number of reactive isocyanate in the component S2 is (1.0-1.05): 1.0; the component S1 is prepared from the following raw materials in parts by weight: 10 to 30 parts of aziridine modified rosin resin solution, 20 to 30 parts of polyether polyol 1, 20 to 40 parts of polyether polyol 2, 10 to 40 parts of polyether polyol 3, 0.2 to 1.0 part of catalyst A and 0.1 to 0.8 part of defoaming agent; wherein the aziridine modified rosin resin solution is prepared from hydroxyethyl aziridine modified rosin resin and a triglycol phosphite solvent; and the component S2 is unsaturated aliphatic isocyanate. The polyurethane resin provided by the invention provides excellent rigidity and light aging resistance for a fiber reinforced composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer synthesis, resin and fiber-reinforced composite material preparation, in particular to a flame-retardant polyurethane resin and a preparation method and application thereof. Background Art

[0002] The design and manufacturing capabilities of large poles and towers are a reflection of a country's industrial level in a specific field. Traditional electric poles are mostly made of reinforced concrete, while signal towers and power grid towers are mostly made of steel. Western European and American countries, including Russia, began to explore the application of composite materials in the field of large poles and towers in the 1980s to solve the problems of reinforced concrete and metal materials in the application process, such as being too heavy to carry, being easily struck by lightning, and not being resistant to corrosion.

[0003] Compared with traditional materials, composite poles and towers have many advantages such as light weight, high strength, corrosion resistance, aging resistance, high and low temperature resistance, etc. They are especially suitable for special environments such as mountainous areas, disaster relief sites, chemical industry areas, saline-alkali lands, and extremely cold and hot areas. In 2022, my country's National Standards Committee issued GB / T41491-2022 "Composite Poles and Towers for Distribution Networks" specifically for the application of power grid poles to guide and regulate the healthy development of the market and technology.

[0004] In the manufacturing process of large composite poles and towers for outdoor use, winding process is a major production process. However, this process requires that the supporting resin must have the characteristics of flame retardancy, long gel time at room temperature, insensitivity to environmental factors such as air, and high toughness. The first three are to ensure that the process can be carried out smoothly, and high toughness is to ensure that the composite products can be prevented from being destroyed by their own high deformation when facing severe weather such as typhoons. Traditional resins such as epoxy resin, unsaturated resin, phenolic resin, etc. can achieve flame retardancy, long gel time, and insensitivity to air, but the low toughness of the resin itself makes the poles and towers easy to break when facing typhoons.

[0005] Therefore, developing a new resin material that can meet the requirements of large-scale pole tower winding process and has excellent flame retardant properties and toughness has become an important issue that needs to be urgently solved in the current field of composite pole tower technology.

[0006] At present, there have been some attempts to improve the flame retardancy by adding modified rosin resin to polyurethane resin. For example, CN106519157A discloses that based on pure rosin resin, phosphorus is introduced into it through ring-opening reaction between epoxy groups and diethyl phosphate after epoxidation of its conjugated double bonds, and then ring-opening polymerization of propylene oxide is carried out through the hydroxyl groups generated by ring opening and the carboxylic acid of rosin itself to obtain a structural flame-retardant rosin-based polyol. However, the rosin-based polyol needs to use a large amount of toluene solvent in the synthesis process, which is not friendly to the environment; the presence of carboxylic acid on rosin resin requires the addition of a large amount of alkaline catalyst in the process of ring-opening synthesis of polyether by propylene oxide, and it is not separated. The remaining alkaline catalyst has a great influence on the reaction of hydroxyl, water and isocyanate groups in the subsequent foam preparation process; the final structure contains only hydroxyl functional groups and does not contain functional double bonds.

[0007] CN101891883A discloses that any of maleopimaric acid, maleopimaric anhydride, and propylenepimaric acid is used as a raw material, reacted with a flame retardant polyol ROH in the presence of a catalyst, and the flame retardant structure of the rosin ternary phenanthrene ring and the flame retardant nitrogen and phosphorus elements are introduced into the flame retardant polyol structure to obtain a reactive flame retardant rosin polyester polyol with a composite flame retardant system. However, the rosin polyester polyol product has a complex structure and a high viscosity, which brings difficulties to its application; the product has a dark color and cannot be used to prepare a light-colored polyurethane product; the final structure of the product contains only hydroxyl functional groups and no reactive double bonds, and the double bonds retained are the products of conjugated double bonds added when the rosin resin is modified, which reduces the functionality of the application.

[0008] CN101693762A discloses that rosin dibasic acid or tribasic acid, alkane diamine, and acid catalyst are added to a pressure-resistant reactor, mixed, heated, stirred, reacted for 3-8 hours, cooled to 100-120°C, added with an alkali catalyst, vacuumed and oxygen-free, and then the temperature is kept at 130-150°C, ethylene oxide and propylene oxide are divided into several times, and the reaction is alternately cyclically introduced in the order of first introducing ethylene oxide and then introducing propylene oxide, and then reduced pressure distillation is performed to obtain a flame-retardant rosin polyether polyol. The synthesis process of the rosin polyether polyol has harsh conditions and high requirements for equipment; the final structure contains only nitrogen elements, and no other flame-retardant elements are used to synergistically improve the flame-retardant effect; the final structure contains only hydroxyl functional groups, and does not contain reactive double bonds, and the double bonds retained are the products of conjugated double bonds added when the rosin resin is modified, which reduces the functionality of the application.

[0009] The flame-retardant rosin polyol prepared by the prior art has high viscosity, dark color, and high catalyst residue, and is only suitable for the preparation of rigid foam applications that are not sensitive to moisture and color, and cannot be used to prepare rigid composite materials that have high requirements for process and raw material quality. In summary, the flame-retardant rosin polyol prepared by the prior art still has many deficiencies in performance and application, and a new type of resin material is urgently needed to meet the requirements of large-scale tower winding process. Summary of the invention

[0010] To solve the above problems, the present invention uses triglycol phosphite prepared by an ester exchange method as a flame retardant and solvent, dissolves rosin in it at a certain temperature, and adds hydroxyethylaziridine, obtains a rosin-modified polymer containing binary active hydrogen and conjugated double bonds through the reaction of carboxylic acid groups with aziridine groups, and applies it as a raw material to a two-component polyurethane resin. The resin containing the rosin-modified polymer in the present invention, combined with the aliphatic isocyanate resin with a low NCO content after modification of the S2 component, has a long operability time and is insensitive to moisture in the air. The cured product and fiber-reinforced composite material products have excellent impact toughness and high flame retardant properties, which fully meet the production process of large pole towers. Compared with common commercially available two-component polyurethane resins, the flame retardant in the present invention is a reactive flame retardant, which can participate in the reaction into the polymer cross-linking network and does not affect the mechanical properties; the S2 component is an aliphatic NCO, which has low activity, is insensitive to moisture, and only provides partial curing and cross-linking. This characteristic provides the system with an extremely long operating time; the introduction of rosin resin, mainly a multi-aliphatic ring structure, gives the material excellent aging resistance, and greatly improves the rigidity and impact toughness of the resin cured product and the fiber-reinforced composite material.

[0011] The following is the synthesis process of rosin with a typical structure modified by hydroxyethylaziridine to form rosin resin modified by hydroxyethylaziridine:

[0012]

[0013] Purpose of the invention: To provide a preparation method and application field of a high-strength two-component aliphatic polyurethane resin with flame retardancy, aging resistance and high impact toughness, so as to solve the problems in the background technology.

[0014] Technical solution:

[0015] The present invention provides a flame retardant two-component aliphatic polyurethane resin, which is prepared by mixing a component S1 and a component S2, wherein the molar ratio of the number of moles of reactive hydroxyl groups in the component S1 to the number of moles of reactive isocyanate in the component S2 is (1.0-1.05):1.0;

[0016] The S1 component includes the following raw materials in parts by weight:

[0017]

[0018] The aziridine-modified rosin resin solution comprises hydroxyethylaziridine-modified rosin resin and triglycol phosphite solvent, and the modified rosin resin is 25-64wt% of the triglycol phosphite solvent;

[0019] The structure of the triglycol phosphite is as follows:

[0020] R is a C2-C8 fatty chain;

[0021] The polyether polyol 1 is selected from a high hydroxyl value polyol with f=3 to 6, and the hydroxyl value range is 480 to 1080 mgKOH / g;

[0022] The polyether polyol 2 is selected from a medium hydroxyl value polyol with f=3 to 4, and the hydroxyl value range is 230 to 380 mgKOH / g;

[0023] The polyether polyol 3 is selected from a low hydroxyl value polyol with f=2 to 3, and the hydroxyl value range is 28 to 112 mgKOH / g;

[0024] The S2 component is an unsaturated aliphatic isocyanate.

[0025] The rosin resin modified with hydroxyethylaziridine is obtained by ring-opening hydroxyethylaziridine and bonding it to the hydroxyl group of the rosin structure.

[0026] As an example, the structure of the hydroxyethylaziridine-modified rosin resin is as follows:

[0027] In some embodiments of the present invention, the preparation of the aziridine-modified rosin resin solution comprises the following steps: adding rosin in an amount of 20 to 50% by weight to triglycol phosphite, heating and stirring to dissolve, and then cooling to room temperature, calculating the number of moles of carboxyl groups according to the acid value of the solution, weighing and adding hydroxyethylaziridine in an amount equal to the number of moles of carboxyl groups, and after the reaction at room temperature is completed, obtaining an aziridine-modified rosin resin solution.

[0028] In some embodiments of the present invention, the preparation of the S2 component comprises the following steps: (1) adding aliphatic isocyanate, unsaturated monoalcohol and inhibitor, heating to 80-120°C, reacting for 4-8 hours, and cooling to below 40°C; (2) adding initiator, stirring evenly to obtain the S2 component.

[0029] In some embodiments of the present invention, the preparation of the S1 component comprises the following steps: adding catalyst A, polyether polyol 1, polyether polyol 2, polyether polyol 3 and a defoamer to an aziridine-modified rosin resin solution in sequence at room temperature, and stirring evenly.

[0030] In some embodiments of the present invention, the triglycol phosphite is prepared by transesterification of triethyl phosphite with diol in the presence of a solid base catalyst. The base catalyst is separated by filtration to reduce the residue of the base catalyst in the synthetic product.

[0031] In some embodiments of the present invention, the catalyst A is a composition of an organotin compound and an organoaluminum compound with low catalytic activity. Specifically, the organotin compound is selected from one of UL-6, UL-28, and UL-29 of Momentive, USA, and the organoaluminum compound is selected from 5218 of KING, USA.

[0032] In some embodiments of the present invention, the defoaming agent is an organic fluorine solution. Specifically, the organic fluorine solution is selected from the H806 product of Nanjing Jufa New Materials Co., Ltd.

[0033] In some embodiments of the present invention, the aliphatic isocyanate is selected from one of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), and dicyclohexylmethyl diisocyanate (HMDI).

[0034] In some embodiments of the present invention, the unsaturated monoalcohol is an acrylate monoalcohol. Specifically, the acrylate monoalcohol is selected from one of hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), hydroxyethyl methacrylate (HEMA) and hydroxypropyl methacrylate (HPMA).

[0035] In some embodiments of the present invention, during the preparation of the S2 component, the added aliphatic isocyanate and unsaturated monoalcohol are equimolar, the added amount of the inhibitor is 100ppm to 500ppm of the total weight of the aliphatic isocyanate and the unsaturated monoalcohol, and the inhibitor is selected from one of hydroquinone, methylhydroquinone, phenol, o-methylhydroquinone, and p-hydroxyanisole.

[0036] In some embodiments of the present invention, the initiator is a peroxide that decomposes at medium to high temperatures. Specifically, the peroxide is selected from one of benzoyl peroxide, dodecyl peroxide, diisopropylbenzene peroxide, tert-butyl perbenzoate, and cumene peroxide. The initiator is added in an amount of 1.5 wt% to 3 wt% of the total weight of the aliphatic isocyanate and the unsaturated monoalcohol.

[0037] The present invention also provides the application of the flame-retardant polyurethane resin. The resin is used as a raw material in various large-scale electric poles, signal towers, elevated frames, storage tanks and other structural parts prepared by winding technology.

[0038] The present invention also provides a fiber-reinforced material, which is made by compounding the above-mentioned aliphatic polyurethane resin and fibers.

[0039] The present invention also provides a method for preparing the above aliphatic polyurethane resin, comprising the following steps: mixing component S1 and component S2, and obtaining the polyurethane resin after curing.

[0040] Beneficial effects:

[0041] Compared with the prior art, the present invention has the following advantages: (1) Compared with cement or steel towers, composite materials are stronger and lighter, are corrosion-resistant, do not require painting and post-maintenance, and combined with operation and maintenance calculations, the overall cost is lower. The products of the present invention are particularly suitable for mountainous areas and disaster relief sites; (2) Compared with epoxy resins, unsaturated resins and phenolic resins, the products of the present invention have no odor and do not release small molecules, have lower VOC and are more environmentally friendly. The key is that the impact toughness is better and can withstand higher-level typhoons while still retaining functionality; (3) Compared with the existing two-component PUR polyurethane resin, the operating time is significantly longer. The product has a longer shelf life and is insensitive to moisture in the air, further improving the product yield. Compared with the existing acrylate-modified hybrid polyurethane resin, the introduction of rosin structure improves aging resistance and impact resistance, further improving the ability of composite products to cope with severe weather. (4) Aziridine-modified rosin resin contains hydroxyl, secondary amino and conjugated double bonds on the aliphatic ring. During the curing process of the two-component polyurethane resin, it can be fixed in the polymer cross-linking network through the reaction of active hydrogen with isocyanate and the reaction of double bond curing, thereby providing excellent rigidity and light aging resistance for the resin cured product and fiber-reinforced composite material. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with the embodiments, and the examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. In the embodiments, specific techniques and reaction conditions are not indicated, and the techniques or conditions or product specifications described in the literature in this area can be carried out. All reagents, instruments or equipment not indicating the manufacturer can be obtained commercially. If not otherwise specified, the percentages in the specification are weight percentages.

[0043] Example 1

[0044] Preparation process of S1 component: 100kg of triethylene glycol phosphite is used as a flame retardant and solvent, 50% weight of rosin (50kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 54mgKOH / g, 12.58kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 100mgKOH / g.

[0045] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 255 mgKOH / g

[0046]

[0047] S2 component: Add 222kg IPDI to the reactor, continue to add 116kg hydroxyethyl acrylate, 169g o-methylhydroquinone with a total weight of 500ppm, raise the temperature to 80°C, react for 8h, cool to below 40°C, add 5.07kg benzoyl peroxide with a total weight of 1.5wt%, stir evenly, discharge, and measure the NCO content to be 12.4%.

[0048] The S1 component and the S2 component were mixed to prepare the resin at a weight ratio of 100:154 and a reactant molar ratio of 1.0:1.0. Four pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin and then a molding process was used to prepare a board with a thickness of about 1mm. The flame retardancy, light aging resistance and mechanical properties were tested.

[0049] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0050] Example 2

[0051] Preparation process of S1 component: 100kg of trioctane phosphite is used as a flame retardant and solvent, 20% weight of rosin (20kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 27.5mgKOH / g, 5.13kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 53mgKOH / g.

[0052] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 386 mgKOH / g

[0053]

[0054]

[0055] S2 component: Add 168kg HDI to the reactor, continue to add 130kg hydroxyethyl methacrylate, and 100ppm methylhydroquinone by total weight, heat to 120°C, react for 4h, cool to below 40°C, add 5.96kg dodecanoyl peroxide (2%), stir evenly, discharge, and measure the NCO content to be 14.09%.

[0056] The S1 component and the S2 component were mixed and prepared with a resin in a weight ratio of 100:195 calculated according to the reactant molar ratio of 1.05:1.0. Four pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin, and then a molding process was used to prepare a board with a thickness of about 1mm, and flame retardancy, light aging resistance and mechanical properties were tested.

[0057] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0058] Example 3

[0059] Preparation process of S1 component: 100kg of tributylene phosphite is used as a flame retardant and solvent, 30% weight of rosin (30kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 38mgKOH / g, 7.67kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 72mgKOH / g.

[0060] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 300 mgKOH / g

[0061]

[0062]

[0063] S2 component: Add 258kg HMDI to the reactor, continue to add 130kg hydroxypropyl acrylate, and 200ppm of p-hydroxyanisole by total weight, raise the temperature to 100°C, react for 6h, cool to below 40°C, add 11.64kg of cumene peroxide with a total weight of 3wt%, stir evenly, discharge, and measure the NCO content to be 10.82%.

[0064] The S1 component and the S2 component were mixed to prepare the resin in a weight ratio of 100:204 and a reactant molar ratio of 1.02:1.0. Four pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin and then a molding process was used to prepare a board with a thickness of about 1mm. The flame retardancy, light aging resistance and mechanical properties were tested.

[0065] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0066] Example 4

[0067] Preparation process of S1 component: 100kg of tripropylene glycol phosphite is used as a flame retardant and solvent, 40% weight of rosin (40kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 47mgKOH / g, 10.22kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 88mgKOH / g.

[0068] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 239 mgKOH / g

[0069]

[0070] S2 component: Add 258kg HMDI to the reactor, continue to add 144kg hydroxypropyl methacrylate, and 400ppm of phenol in total weight, heat to 100°C, react for 6h, cool to below 40°C, add 9.25kg of tert-butyl peroxybenzoate with a total weight of 2.3wt%, stir evenly, discharge, and measure the NCO content to be 10.82%.

[0071] The S1 component and the S2 component were mixed to prepare the resin according to the reactant molar ratio of 1.02:1.0. After 4 pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin, a molding process was used to prepare a board with a thickness of about 1mm, and flame retardancy, light aging resistance and mechanical properties were tested.

[0072] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0073] Example 5

[0074] Preparation process of S1 component: 100kg of trihexylene glycol phosphite is used as a flame retardant and solvent, 25% weight of rosin (25kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 33mgKOH / g, 6.41kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 63mgKOH / g.

[0075] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 256 mgKOH / g

[0076]

[0077] S2 component: Add 222kg IPDI to the reactor, continue to add 144kg hydroxypropyl methacrylate, and 150ppm hydroquinone by total weight, raise the temperature to 110°C, react for 5h, cool to below 40°C, add 9.89kg cumene peroxide with a total weight of 2.7wt%, stir evenly, discharge, and measure the NCO content to be 11.48%.

[0078] The S1 component and the S2 component were mixed to prepare the resin at a molar ratio of 1.01:1.0 and a weight ratio of 100:165. After 4 pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin, a molding process was used to prepare a board with a thickness of about 1mm, and flame retardancy, light aging resistance and mechanical properties were tested.

[0079] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0080] Example 6

[0081] Preparation process of S1 component: 100kg of tripentanediol phosphite is used as a flame retardant and solvent, 45% weight of rosin (45kg) is added, the temperature is raised to 60°C, stirred for 1h to dissolve, and the temperature is lowered to room temperature. At this time, the acid value of the solution is about 51mgKOH / g, 11.49kg of hydroxyethyl aziridine (the molar ratio of carboxyl group to aziridine group is the same) is added, and the reaction is carried out at room temperature for 2h to obtain an aziridine-modified rosin resin solution with a hydroxyl value of about 95mgKOH / g.

[0082] Add the following other components in the following proportions and stir evenly. The hydroxyl value of the mixture is 243 mgKOH / g

[0083]

[0084] S2 component: Add 168kg HDI to the reactor, continue to add 144kg hydroxypropyl methacrylate, and 450ppm of hydroquinone by total weight, raise the temperature to 90°C, react for 5h, cool to below 40°C, add 5.62kg of tert-butyl perbenzoate with a total amount of 1.8wt%, stir evenly, discharge, and measure the NCO content to be 13.46%.

[0085] The S1 component and the S2 component were mixed and prepared with a resin in a weight ratio of 100:130 calculated according to the reactant molar ratio of 1.04:1.0. Four pieces of 200mm*200mm glass fiber cloth were fully impregnated with the resin, and then a molding process was used to prepare a board with a thickness of about 1mm, and flame retardancy, light aging resistance and mechanical properties were tested.

[0086] The above mixed resin was used with the internal curing winding equipment of Wuhan Jiudi Company to prepare a 12m long composite pole with a base diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm, and a load test was carried out.

[0087] Comparative Example 1

[0088] The flame-retardant resin component of this comparative example is epoxy resin E51, and the addition amount of the general additive flame retardant (TDCP, Zhejiang Wansheng Company) is 0.5 parts; the other steps same as Example 1 are adopted to prepare 1mm*200mm*200mm plates and composite poles with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0089] Comparative Example 2

[0090] The flame-retardant resin component of this comparative example is unsaturated polyester resin (type 196), and the addition amount of the general additive flame retardant (TDCP, Zhejiang Wansheng Company) is 0.2 parts; the other steps same as Example 2 are adopted to prepare 1mm*200mm*200mm plates and composite poles with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0091] Comparative Example 3

[0092] The flame-retardant resin component of this comparative example is vinyl resin SWANCOR901, and the addition amount of the general additive flame retardant (TDCP, Zhejiang Wansheng Company) is 1.0 part; the other steps same as Example 3 are adopted to prepare 1mm*200mm*200mm plates and composite poles with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0093] Comparative Example 4

[0094] The flame-retardant resin component of this comparative example is phenolic resin PF131, and the addition amount of the general additive flame retardant (TDCP, Zhejiang Wansheng Company) is 0.7 parts; the other steps same as Example 4 are adopted to prepare 1mm*200mm*200mm plates and composite poles with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0095] Comparative Example 5

[0096] The flame-retardant resin component of this comparative example is an unmodified aliphatic polyurethane two-component resin (CN110922091A Example 1), and the addition amount of a universal additive flame retardant (TDCP, Zhejiang Wansheng Company) is 0.6 parts; the other steps same as Example 5 are used to prepare a 1mm*200mm*200mm plate and a composite pole with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0097] Comparative Example 6

[0098] The flame-retardant resin component of this comparative example is an acrylate-hybridized aliphatic polyurethane two-component resin (CN101787170A Example 1, without rosin structure), and the addition amount of a universal additive flame retardant (TDCP, Zhejiang Wansheng Company) is 0.8 parts; the other steps same as Example 6 are adopted to prepare a 1mm*200mm*200mm plate and a composite pole with a bottom diameter of 300mm, a tip diameter of 200mm, and a thickness of 10mm.

[0099] Performance comparison

[0100] Table 1. Performance comparison of examples and comparative examples

[0101]

[0102] Oxygen index test standard: GB / T 8924-2005

[0103] Flame retardant grade test method: UL94

[0104] Mechanical properties retention rate test standard: GB / T 1447-2005

[0105] Light aging test method: IEC 61215-2:2016

[0106] Impact strength test method: GB / T 1451-2005

[0107] It can be seen that the phosphorus-containing polyol prepared by the present invention has the same flame retardant effect as the traditional flame retardant products that have been verified by the market. On this basis, its mechanical properties are significantly improved, which solves the problem that the added flame retardant causes the mechanical properties of the composite material products to decrease. Due to the introduction of the rosin structure, its light aging resistance and the impact resistance of the resin cured product are significantly improved.

[0108] Composite material load test method: fix the bottom end of the composite material, apply tension to the top end, and test the actual load value of the top end of the composite material at different deformation points. The test data are shown in Table 2.

[0109] Table 2 Comparison of deformation and load performance of pole products in the embodiment and comparative example

[0110] 0.5m 1.0m 1.5m 2.0m 2.5m 3.0m Example 1 Load (KN) 5,533 10,265 16,333 22,588 28,342 33,897 Example 2 Load (KN) 5,487 10,378 15,492 22,087 27,696 31,588 Example 3 Load (KN) 5,612 10,199 15,888 22,121 28,034 32,776 Example 4 Load (KN) 5,588 10,377 16,109 21,972 28,534 33,066 Example 5 Load (KN) 5,679 10,421 16,775 22,356 28,741 33,288 Example 6 Load (KN) 5,429 10,763 16,498 22,765 27,805 33,418 Comparative Example 1 Load (KN) 4,218 7,659 10,265 14,319 18,768 22,004 Comparative Example 2 Load (KN) 4,389 7,763 fracture - - - Comparative Example 3 Load (KN) 4,632 7,538 10,639 15,121 18,643 22,398 Comparative Example 4 Load (KN) 4,823 8,045 11,769 fracture - - Comparative Example 5 Load (KN) 4171 7384 10021 13886 17854 21078 Comparative Example 6 Load (KN) 4532 7749 11186 15630 19218 22667

[0111] It can be seen from Table 2 that the comparative example adds a large amount of additive flame retardant, which acts as a plasticizer in the solidification system, making the overall load capacity of the tower significantly lower than that of the corresponding embodiment. However, all the flame retardants in the embodiment are reactive, and can be completely connected to the solidification network by covalent bonds after solidification. Combined with the multiple aliphatic ring structures of rosin, the composite tower has excellent load capacity.

[0112] In addition, unsaturated polyester resin-based and phenolic resin-based composite towers also broke.

Claims

1. A flame retardant two-component aliphatic polyurethane resin, characterized in that: The resin is prepared by mixing a component S1 and a component S2, wherein the molar ratio of the number of moles of the reactive hydroxyl group in the component S1 to the number of moles of the reactive isocyanate in the component S2 is (1.0-1.05):1.0; The S1 component includes the following raw materials in parts by weight: The aziridine-modified rosin resin solution comprises hydroxyethylaziridine-modified rosin resin and triglycol phosphite solvent, and the modified rosin resin is 25-64wt% of the triglycol phosphite solvent; The structure of the triglycol phosphite is as follows: R is a C2-C8 fatty chain; The polyether polyol 1 is selected from high hydroxyl polyols with f=3-6, and the hydroxyl value range is 480-1080 mgKOH / g; the polyether polyol 2 is selected from medium hydroxyl polyols with f=3-4, and the hydroxyl value range is 230-380 mgKOH / g; the polyether polyol 3 is selected from low hydroxyl polyols with f=2-3, and the hydroxyl value range is 28-112 mgKOH / g; the S2 component is an unsaturated aliphatic isocyanate, and the preparation of the S2 component includes the following steps: (1) adding aliphatic isocyanate, unsaturated monoalcohol and inhibitor, heating to 80-120°C, reacting for 4-8h, and cooling to below 40°C; (2) adding an initiator, stirring evenly, and obtaining the S2 component.

2. The resin according to claim 1, characterized in that The preparation of the aziridine-modified rosin resin solution comprises the following steps: adding rosin of 20 to 50% by weight to triglycol phosphite, heating and stirring to dissolve, then cooling to room temperature, calculating the number of moles of carboxyl groups according to the acid value of the solution, weighing hydroxyethylaziridine of the same mole number as the carboxyl groups, and adding the aziridine-modified rosin resin solution after the reaction at room temperature is completed.

3. The resin according to claim 1, characterized in that The triglycol phosphite is prepared by transesterification reaction of triethyl phosphite and diol under the action of solid alkali catalyst.

4. The resin according to claim 1, characterized in that The catalyst A is a composition of an organotin compound and an organoaluminum compound with low catalytic activity.

5. The resin according to claim 1, characterized in that The defoaming agent is an organic fluorine solution.

6. The resin according to claim 1, characterized in that The aliphatic isocyanate is selected from one of isophorone diisocyanate, hexamethylene diisocyanate and dicyclohexylmethyl diisocyanate.

7. The resin according to claim 1, characterized in that The unsaturated monoalcohol is an acrylic ester monoalcohol.

8. The resin according to claim 1, characterized in that During the preparation of the S2 component, the added aliphatic isocyanate and unsaturated monoalcohol are equimolar, the added amount of the inhibitor is 100ppm to 500ppm of the total weight of the aliphatic isocyanate and the unsaturated monoalcohol, and the inhibitor is selected from one of hydroquinone, methylhydroquinone, phenol, o-methylhydroquinone, and p-hydroxyanisole.

9. The method for preparing the resin according to any one of claims 1 to 8, comprising the following steps: The S1 component and the S2 component are mixed and cured to obtain the polyurethane resin; wherein the preparation of the S1 component comprises the following steps: at room temperature, a catalyst, polyether polyol 1, polyether polyol 2, polyether polyol 3 and a defoaming agent are sequentially added to an aziridine-modified rosin resin solution, and the mixture is stirred evenly.

10. Use of the resin according to any one of claims 1 to 8, characterized in that: The resin is used as a raw material in various large-scale electric poles, signal towers, elevated frames, storage tanks and other structural parts prepared by winding technology.

Citation Information

Patent Citations

  • Rosin polyether glycol used for flame-retardant hard polyurethane foaming plastic and preparation method thereof

    CN101693762A

  • Preparation method of alcohol soluble normal-temperature curing bi-component polyurethane-acrylate resin

    CN101787170A

  • Rosin polyester polyol for flame-retardant rigid polyurethane foam plastic and preparation method and application thereof

    CN101891883A

  • Structure flame retardant rosin-based polyhydric alcohol for hard polyurethane foam and preparation method and application thereof

    CN106519157A

  • Two-component polyurethane composition for concrete modification and preparation method thereof

    CN110922091A